2011
DOI: 10.1371/journal.pone.0016861
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular DNA Is Essential for Maintaining Bordetella Biofilm Integrity on Abiotic Surfaces and in the Upper Respiratory Tract of Mice

Abstract: Bacteria form complex and highly elaborate surface adherent communities known as biofilms which are held together by a self-produced extracellular matrix. We have previously shown that by adopting a biofilm mode of existence in vivo, the Gram negative bacterial pathogens Bordetella bronchiseptica and Bordetella pertussis are able to efficiently colonize and persist in the mammalian respiratory tract. In general, the bacterial biofilm matrix includes polysaccharides, proteins and extracellular DNA (eDNA). In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 103 publications
(76 citation statements)
references
References 55 publications
2
72
0
2
Order By: Relevance
“…We have shown that both B. bronchiseptica and B. pertussis are capable of forming biofilms in the upper respiratory tract of infected animals (13,14,53). These findings, combined with the presence of clusters, microcolonies, and tangles of B. bronchiseptica and B. pertussis bacteria in explant tissues and nasal biopsy specimens of patients, strengthen the hypothesis that Bordetella bacteria utilize biofilms as a means to persist and circulate between their mammalian hosts (22,47,54).…”
supporting
confidence: 65%
“…We have shown that both B. bronchiseptica and B. pertussis are capable of forming biofilms in the upper respiratory tract of infected animals (13,14,53). These findings, combined with the presence of clusters, microcolonies, and tangles of B. bronchiseptica and B. pertussis bacteria in explant tissues and nasal biopsy specimens of patients, strengthen the hypothesis that Bordetella bacteria utilize biofilms as a means to persist and circulate between their mammalian hosts (22,47,54).…”
supporting
confidence: 65%
“…B. pertussis strains were maintained on Bordet-Gengou agar (BG) supplemented with 10% defibrinated sheep blood. Liquid cultures were grown in Stainer-Scholte (SS) broth with heptakis (2,6-di-O-methyl-␀-cyclodextrin) (21,22). Escherichia coli strains were grown in Luria-Bertani medium.…”
Section: Methodsmentioning
confidence: 99%
“…If extracellular DNA is a major structural component of the biofilm matrix, as seen for other bacterial biofilms (365), it could serve as a target for treatment with DNase I. DNase I has been reported to disrupt biofilms (65). D-Amino acids have been reported to prevent biofilm formation (177).…”
Section: Molecular Mechanisms Involved In Pathogenesis Biofilmsmentioning
confidence: 99%